Not so shy - Nimrodi, Noa, 1969- (Kar-Ben Publishing, an imprint of Lerner Publishing Group, Inc., 2023)
Twelve-year-old Shai hates having to move to America and is determined to find a way get back home to Israel--until she starts opening up to new experiences and friendships.